EMPLOYMENT PROTECTION IN THE CONSTRUCTION SECTOR IN WAGE DISPUTES FROM THE MAQASID SYARI'AH PERSPECTIVE - Krisnadi Kusuma Suwandi; Zaid Alfauza Marpaung (Program Pascasarjana UIN Sumatera Utara, 2026)
Informal construction workers constitute one of the most vulnerable labor groups, particularly in matters related to wage rights. The absence of clear contracts, the dominant position of employers, and the limited availability of legal protection mechanisms place these workers in a weak bargaining position. This study aims to analyze the forms of legal protection available to informal construction workers in wage disputes based on Indonesian positive law and to compare them with the perspective of Maqasid al-Shari’ah. This research employs an empirical legal method with a sociological approach. The findings reveal that although legal protection is normatively provided through labor regulations, its implementation remains ineffective due to weak supervision, the absence of written agreements, low legal literacy among workers, and highly hierarchical employment relations. From the perspective of Maqasid al-Shari’ah, practices such as unilateral wage deductions, delayed payments, and unclear employment agreements constitute violations of the principles of hifz al-māl (protection of wealth) and hifz al-nafs (protection of life), and contradict the value of justice (‘adl).